2009
DOI: 10.1590/s0103-97332009000100017
|View full text |Cite
|
Sign up to set email alerts
|

Optimal paths for minimizing lost available work during heat transfer processes with a generalized heat transfer law

Abstract: A common of finite-time heat transfer processes between high-and low-temperature sides with a generalized heat transfer law [q ∝ (∆(T n )) m ] are studied in this paper. The optimal heating and cooling configurations for minimizing lost available work are derived for the fixed initial and final temperatures of the working fluid of the system (low-temperature side). Optimal paths are compared with the common strategies of constant heat flux, constant source (reservoir) temperature and the minimum entropy genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 29 publications
0
7
0
2
Order By: Relevance
“…Comparison between eqs. (24) and (31) shows that the entransy dissipation corresponding to the optimal heat exchange strategies of minimum entransy dissipation during the phase change processes is 8/9 of that corresponding to constant reservoir temperature operations, which is also independent of all system parameters. Combining eq.…”
Section: Constant Reservoir Temperature Operationsmentioning
confidence: 95%
See 1 more Smart Citation
“…Comparison between eqs. (24) and (31) shows that the entransy dissipation corresponding to the optimal heat exchange strategies of minimum entransy dissipation during the phase change processes is 8/9 of that corresponding to constant reservoir temperature operations, which is also independent of all system parameters. Combining eq.…”
Section: Constant Reservoir Temperature Operationsmentioning
confidence: 95%
“…Nummedal [28] and Johannessen [29] investigated a class of plug flow reactors including the irreversibilities of heat transfer, fluid flow pressure drop and various chemical reactions, and derived the optimal configuration of the external furnace gases temperature for minimizing entropy generation. Chen et al [30] and Xia et al [31] derived optimal paths of heat transfer processes with a generalized heat transfer law [ ( ) n m q T ∝ Δ ] [14] for minimizing entropy generation [30] and minimizing exergy loss [31], respectively. Gordon et al [32] derived the optimal external heat reservoir temperature profiles of liquid-solid phase change processes for minimizing entropy generation.…”
Section: Introductionmentioning
confidence: 99%
“…Fixed T 1f (t 1 = 150 s) References [25,65,[69][70][71] showed that the difference of reciprocal temperatures of the heat reservoir and the working fluid for the maximum work output of the reciprocating endoreversible heat engine with the linear phenomenological heat transfer law is a constant, and the reservoir temperature decreases with the time linearly; Refs. [3,63,64,[72][73][74] also showed that the difference of reciprocal temperatures of the high-and low-temperature sides for the minimum entropy generation of heat transfer processes with the linear phenomenological heat transfer law is a constant, and the high-temperature reservoir temperature decreases with the time linearly.…”
Section: Numerical Examples For the Multistage Heat Engines With The mentioning
confidence: 96%
“…], Chen et al [38] and Xia et al [39] derived the optimal temperature configurations of heat transfer processes for minimum entropy generation [38] and minimum lost available work [39]. Xia et al [40] further investigated the minimum entransy dissipation of heat transfer processes with the generalized radiative heat transfer law.…”
Section: Introductionmentioning
confidence: 99%